PENGGUNAAN METODE JARIMATIKA DALAM MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN PADA SISWA TUNARUNGU KELAS VI DI SKH SAMANTHA KOTA SERANG (Single Subject Research di Kelas VI SKh Samantha Kota Serang) - Syifa Tasliah; Dr. Hj. Isti Rusdiyani, M.Pd; Reza Febri Abadi, M.Pd (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2018)
ABSTRACT This research aims to increase multiplication numeracy skills use arithmetic finger method towards 6th grade students with hearing impairment of Samantha special needs school, Serang city. The purpose of this study was seen from the student’s initial skills before and after giving the application of arithmetic finger based on the criteria for using arithmetic finger, namely the increase in student’s multiplication numeracy skills. The research method is experiment with types of research Single Subject Research (SSR) with design of A-B-A. The research subject is a student of 6th grade at Samantha special needs school, Serang city. The research data collection is through written test and observation. The research data analysis use of descriptive statistical analysis. The result showed an use arithmetic finger method can increase multiplication numeracy skills towards 6th grade students with hearing impairment of Samantha special needs school, Serang city. This is indicated by (1) Increased sequential level of the A-B-A phase, which is 38, 75%, 70%, and 90%, (2) Changes in data stability at each phase show data that is stable (100%) and shows an ascending direction, (3) The change in the data level between phase A1/B is (+15%) and between phases B/A2 is (+10%), (4) The percentage of overlap data obtained is 0% in the A1/B phase and B/A2 phase, and (5) Students feel happy in using the arithmethic finger method.